Peningkatan Sifat Malu (Al-Haya’) Pada Mahasiswa Melalui Layanan Bimbingan Kelompok Berbasis Hadits - Zhila Jannati (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2022)
In its journey, disobedience and goodness are choices for humans. The difference is, someone who has a shy nature (al-haya') will firmly choose goodness for his life. Because, he fears his Lord and will do something that is only in accordance with what Allah swt has. commanded and will abstain from all that He forbids. This is a high level of shame that actually must be embedded in humans, namely shame because they feel close to Allah swt so that they are able to witness the presence of Allah swt. The purpose of this study was to find out how to increase shyness (al-haya') in students through hadith-based group guidance services. The research method that researchers use is descriptive research method. Data collection techniques used are observation and interview techniques. While the researchers took the subject of the students of the Faculty of Da'wah and Communications at UIN Raden Fatah Palembang. The data analysis technique uses three stages, namely reduction, data display and conclusion drawing (verification). This study obtained results, namely (a) hadith-based group guidance has been carried out by passing through four stages, namely the formation stage, transition stage, activity stage, and termination stage, and (b) the student's shyness has increased where his soul has been controlled and he has felt not happy, uncomfortable, and depressed when doing things that are forbidden by Allah swt. (bad deeds or immorality), as well as a desire to leave or stay away from bad things carefully.